Virtual choir: Rehearsal methodology - Oliveira, Jetro Meira de (Revista Hipótese, 2022)
During the 2020-2021 period of the COVID-19 pandemic it became common the production virtual choirs in video format of mosaic. Although it is possible to obtain similar recording results to those of an in presence choir, the virtual choir format presentes challenges for the development of a rehearsal process. This essay proposes a virtual rehearsal methodology which aproximates the benefits of an in presence rehearsal, listing different approaches to overcome the absence of the natural sound reference of a face-to-face rehearsal process. The application of this methodology and results achieved with the UNESP Chamber Choir, Campus São Paulo, during the 2021 school year are also presented.
Keywords: Virtual choir; Rehearsal methodology; Music and technology